2016
DOI: 10.1039/c5nj03338a
|View full text |Cite
|
Sign up to set email alerts
|

Non-mercury catalytic acetylene hydrochlorination over a NH4F–urea-modified Pd/HY catalyst for vinyl chloride monomer production

Abstract: The modification of NH4F and urea significantly enhances the stability of a Pd/HY catalyst for acetylene hydrochlorination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Wang et al introduced K and NH 4 F promoters in Pd/HY catalyst. The presence of K and NH 4 F promoters exhibit a good effect on the acidity on the surface of catalyst and effectively inhibit the run off of Pd component [38][39][40][41][42][43]. Hu et al reported an (NPs)/surfactant ionic liquids system and constructed an effective redox cycle in catalytic system [61].…”
Section: Characterization Of Pd-based Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al introduced K and NH 4 F promoters in Pd/HY catalyst. The presence of K and NH 4 F promoters exhibit a good effect on the acidity on the surface of catalyst and effectively inhibit the run off of Pd component [38][39][40][41][42][43]. Hu et al reported an (NPs)/surfactant ionic liquids system and constructed an effective redox cycle in catalytic system [61].…”
Section: Characterization Of Pd-based Catalystsmentioning
confidence: 99%
“…Recent studies have shown that Pd supported catalysts could be an efficient, low-cost, mercury-free alternative for acetylene hydrochlorination [29,[36][37][38][39][40][41][42][43]. However, the inherent volatilization of Pd component limits the use of Pd-based catalysts for producing VCM [36][37][38][39][40][41][42][43]. We have previously reported a supported-ionic-liquid-phase (SILP) Pd catalysts (Pd-IL/AC) for the acetylene hydrochlorination [29].…”
Section: Introductionmentioning
confidence: 99%
“…Since Hutchings et al suggested that the activities of metal catalysts were associated with the standard electrode potentials of the related metal ions, 3 numerous studies have been carried out to develop non-mercury catalysts for efficient and sustainable hydrochlorination of acetylene in recent years, such as Au, [4][5][6][7][8][9][10][11] Pd, [12][13][14][15][16][17][18][19] Pt, 20 Ru, 21 Bi, 22 Cu, 23,24 etc. Based on the detailed study by Hutchings' team, 3 metal chloride/activated carbon catalysts (including Pd 2+ , Hg 2+ , Cu 2+ , Cu + , Ag + ) had superior catalytic activity and the order of their activities was Pd 2+ > Hg 2+ > Cu 2+ > Cu + > Ag + .…”
mentioning
confidence: 99%
“…Therefore, palladium-based catalysts were reported to be active for acetylene hydrochlorination. [12][13][14][15][16][17][18][19] Wang et al prepared Pd-based/C catalysts via impregnation method and suggested that the Pd loss and the carbon deposition were main reasons for the catalyst deactivation, and the adding of K and La could improve the stability and regeneration of Pd/C catalysts. 18 Mitchenko et al reported that Pd(II) chloro complexes were the active sites of catalysts 19 and the (NH 4 ) 2 PdCl 4 complex could stabilize the Pd species resulted in improving the catalytic performance over carbon-based materials.…”
mentioning
confidence: 99%
See 1 more Smart Citation